2022
DOI: 10.1186/s12877-022-02801-5
|View full text |Cite
|
Sign up to set email alerts
|

Physical capability in a rural birth cohort at the age of 52: association with early environmental, nutritional, and developmental factors

Abstract: Introduction Midlife physical capability (PC) is associated with developmental factors in the populations of economically developed countries. As far as we know, there is no information for rural populations of low- and middle-income countries. The aim of the study was to investigate the influence of pre- and postnatal factors on midlife objective measures of PC in a 1966–67 birth cohort from a Mexican rural community. The hypothesis was that adverse developmental conditions are associated with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 59 publications
1
0
0
Order By: Relevance
“…Among the CVH metrics, BMI, blood glucose, and total cholesterol showed a better trend with increased grip strength. Previous studies have suggested that poor rural family environment and low nutritional status of parents were negatively associated with midlife physical capability (30). Moreover, similar to some studies, we found that grip strength may be an under-recognized and controllable determinant of cardiometabolic risk factors in middle-aged and older adults in rural China (31).…”
Section: Discussionsupporting
confidence: 87%
“…Among the CVH metrics, BMI, blood glucose, and total cholesterol showed a better trend with increased grip strength. Previous studies have suggested that poor rural family environment and low nutritional status of parents were negatively associated with midlife physical capability (30). Moreover, similar to some studies, we found that grip strength may be an under-recognized and controllable determinant of cardiometabolic risk factors in middle-aged and older adults in rural China (31).…”
Section: Discussionsupporting
confidence: 87%